James and the giant peach : a children's story - Dahl, Roald, 1916-1990.; Burkert, Nancy Ekholm (New York : Puffin, 1988)
Wonderful adventures abound after James escapes from his fearsome aunts by rolling away in a giant peach.
Book Links (A.L.A.).
Horn Book.
Wilson's Children.
4.5
7.7
3-6.
Keywords: Fantasy; Fantastic fiction